2011
DOI: 10.1017/s1366728911000332
|View full text |Cite
|
Sign up to set email alerts
|

Self-ratings of spoken language dominance: A Multilingual Naming Test (MINT) and preliminary norms for young and aging Spanish–English bilinguals

Abstract: This study investigated correspondence between different measures of bilingual language proficiency contrasting self-report, proficiency interview, and picture naming skills. Fifty-two young (Experiment 1) and 20 aging (Experiment 2) Spanish-English bilinguals provided self-ratings of proficiency level, were interviewed for spoken proficiency, and named pictures in a Multilingual Naming Test (MINT, and in Experiment 1 also the Boston Naming Test; BNT). Self-ratings, proficiency interview, and the MINT did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
401
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(457 citation statements)
references
References 49 publications
26
401
2
3
Order By: Relevance
“…Importantly, pupil sizes during the baseline period did not differ across groups (p > 0.96). For each of the three dependent measures (percentage of pupil size change, voice onset latency and utterance duration), trials in which the values exceeded more than ±2.5 standard deviations from the mean for each participant in each *Score corresponds to the number of correctly named drawings in the bilingual picture-naming test used to assess participants' vocabulary in each language (see Gollan et al, 2012) condition were considered outliers and were subsequently discarded from the analysis (percentage of pupil change: 1.63 % of the trials; voice onset latency: 1.36 % of the trials; utterance duration: 2.71 % of the trials). The remaining data were analyzed in a series of ANOVAs following a 2 × 2 Language (Native|Foreign) × Statement (True|False) design.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, pupil sizes during the baseline period did not differ across groups (p > 0.96). For each of the three dependent measures (percentage of pupil size change, voice onset latency and utterance duration), trials in which the values exceeded more than ±2.5 standard deviations from the mean for each participant in each *Score corresponds to the number of correctly named drawings in the bilingual picture-naming test used to assess participants' vocabulary in each language (see Gollan et al, 2012) condition were considered outliers and were subsequently discarded from the analysis (percentage of pupil change: 1.63 % of the trials; voice onset latency: 1.36 % of the trials; utterance duration: 2.71 % of the trials). The remaining data were analyzed in a series of ANOVAs following a 2 × 2 Language (Native|Foreign) × Statement (True|False) design.…”
Section: Resultsmentioning
confidence: 99%
“…Among the group of bilinguals we studied, the MiNT (Gollan et al, 2011), BDS (Dunn and Fox Tree, 2009), and reported age of English acquisition were highly correlated with one another, so all measures of bilingual dominance behaved similarly to the age of acquisition effects (Table 1). We report correlations with age of acquisition due to theoretical interest.…”
Section: Language Measuresmentioning
confidence: 87%
“…For bilingual participants, we assessed the relative dominance of English and Korean in two ways. Each participant completed a Bilingual Dominance Scale (BDS) (Dunn and Fox Tree, 2009) and a picture naming task assessing lexical inventory (MiNT) in English and Korean (modified from Gollan et al, 2011 by removing words that are cognates in English and Korean). Their BDS was scored as described in Dunn and Fox Tree (2009), and recorded as Korean score minus English score.…”
Section: Language Background Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were exposed to Spanish from a very early age (M = 0.76 years, SE = 0.2, max = 7) and showed very high overall proficiency in Spanish, as assessed using the BEST test (an adaptation of the MINT multilingual naming task for Basque, English, and Spanish; Duñabeitia, Casaponsa, Dimitropoulou, Martí, Larraza, & Carreiras, 2014;Gollan, Weissberger, Runnqvist, Montoya, & Cera, 2012; M = 76.1/77, SE = 0.2) and via in-person interviews that assessed fluency (M = 4.96/ 5, SE = 0.02). Participants were recruited at the University of the Basque Country in San Sebastián (UPV/EHU-Donostia), and were either completing or had recently completed an undergraduate degree.…”
Section: Methodsmentioning
confidence: 99%